2014
DOI: 10.1007/s00586-014-3431-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic study of the relation between the instantaneous center of rotation and degenerative changes in the cervical intervertebral disc

Abstract: Baseline data for Chinese cervical spine ICRs were established for the third through eighth decade of life, including age-related changes and the kinematic effects of degenerative change on the ICR in the functional spine unit. These findings should be considered in clinical practice and when designing disc prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
4
27
0
Order By: Relevance
“…During flexion\extension, as expected, the HAM in each intervertebral motion segment was nearly perpendicular to the sagittal plane of the inferior bone for each motion segment. The intersection of the HAM vector and the sagittal plane during flexion\extension was in agreement with previous reports that calculated a single center of rotation point using static full flexion and full extension radiographs (Amevo et al, 1991;Liu et al, 2014;van Mameren et al, 1992), as well as the centrode during dynamic flexion\extension in an older group of individuals (Anderst et al, 2013a). In each of these studies, the center or rotation (or the centrode, in the case of the dynamic motion study) was located progressively more superior and anterior with respect to the inferior bone in each motion segment from C2-C3 to C6-C7.…”
Section: Discussionsupporting
confidence: 90%
“…During flexion\extension, as expected, the HAM in each intervertebral motion segment was nearly perpendicular to the sagittal plane of the inferior bone for each motion segment. The intersection of the HAM vector and the sagittal plane during flexion\extension was in agreement with previous reports that calculated a single center of rotation point using static full flexion and full extension radiographs (Amevo et al, 1991;Liu et al, 2014;van Mameren et al, 1992), as well as the centrode during dynamic flexion\extension in an older group of individuals (Anderst et al, 2013a). In each of these studies, the center or rotation (or the centrode, in the case of the dynamic motion study) was located progressively more superior and anterior with respect to the inferior bone in each motion segment from C2-C3 to C6-C7.…”
Section: Discussionsupporting
confidence: 90%
“…Another study using the same subjects of this study showed C3/C4 and C4/C5 had greater the anterior-posterior (AP) movement (4.8mm, 4.8mm, respectively) than C5/C6 and C6/C7 (3.7mm, 2.4mm, respectively) during neck flexion-extension, but the superior-inferior (SI) movement of all segment levels was similar (1.7-1.8mm) [19]. During in vivo dynamic flexion-extension, the ICRs of all sub-axial cervical spinal segments were shown to locate anteriorly to the posterior edges of the vertebral bodies [20, 21]. Anderst et al [21] found that the range of the ICR motion in the SI direction was lower than that in AP direction, and the range of the ICR motion in the AP direction at C3/C4 and C4/C5 was greater than that at C5/C6 and C6/C7.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 A pre vious study by our team has shown the relation between the instantaneous center of rotation and cervical disc de generation in asymptomatic subjects. 14 In this study, we performed radiographic studies of the cervical spines of 212 asymptomatic volunteers and demonstrated the effect of disc degeneration on segmental ROM, based on a scor ing system for cervical disc degeneration, 25 which can be used to assess the degree of cervical disc degeneration for 3 independent variables.…”
mentioning
confidence: 99%